Finance and Development, December 2005. (Finance and Development; Finance and Development ;, 2005)
This paper reviews the resurgence of Latin America. The paper highlights that much of the region has witnessed a swift and robust recovery from the successive financial crises of 2001-02. Within two years, the region's economic growth reached 5.6 percent in 2004, a 24-year high. Growth rates of about 4 percent in 2005 and 3 3/4 percent projected for 2006 are well above historical averages. Mexico and South American countries have gained, in particular, from the surge in fuel, food, and metals prices, and have generally been able to exploit these opportunities by expanding production.